Improving student’s self-efficacy through inquiry learning model and modeling in physical education - Hikmad Hakim; Hasmyati Hasmyati; Muhammad Zulfikar; Nur Indah Atifah Anwar; Hezron Alhim Dos Santos; Alimin Hamzah (Jurnal Cakrawala Pendidikan, 2023)
The study aims to reveal the effect of inquiry learning model with modeling application to improve students' self-efficacy. Single-mastery and multiple-coping are used in the modeling. The study used nonequivalent pre-test and post-test control group design. The first experimental group received the inquiry learning model treatment with single-mastery modeling. The second group received received the inquiry learning model treatment with multiple-coping modeling. The direct learning model applied to the control group. Eighty seven students from three classes were taken as research sample using cluster random sampling technique. The treatment lasted for six meetings which were divided into one meeting every week. The instrument used is the physical education self-efficacy scale which was developed in this study based on Bandura's self-efficacy theory. Paired sample t-test and ANCOVA were used to analyze the data. In the two experimental groups, there was significant increase in students' self-efficacy through the application of the inquiry learning model with single-mastery modeling and the inquiry learning model with multiple-coping modeling. Inquiry learning model with multiple-coping modeling is more effective in increasing students' self-efficacy than inquiry learning model with single-mastery modeling and direct learning model.